Towards DSM‐V: considering other withdrawal‐like symptoms of pathological gambling disorder - Cunningham‐Williams, Renee M. (Int J Methods Psychiatr Res, 2009)
Despite clinical reports of other withdrawal‐like symptoms, the DSM‐IV considers only restlessness/irritability as a withdrawal‐like criterion comprising pathological gambling disorder (PGD). We explored whether this criterion should be broadened to include other gambling withdrawal‐like symptoms. Community‐recruited adult gamblers (n = 312) participated in telephone interviews about gambling and related behaviors as a part of a larger psychometric study. Frequency and chi‐square analyses described the association of gambling withdrawal‐like symptoms by gambling disorder status. Multinomial forward selection logistic regression obtained a multivariate model describing the simultaneous relationship between these symptoms and gambling disorder status. One‐quarter of the sample experienced the DSM‐IV PGD criterion of restlessness/irritability. However, 41% experienced additional gambling withdrawal‐like symptoms when attempting to quit or control gambling. A model including restlessness/irritability and three additional non‐DSM‐IV withdrawal‐like symptoms (i.e. feelings of anger, guilt, and disappointment) is a stronger model of gambling disorder (χ(2) = 217.488; df = 8, p < 0.0001; R (2) = 0.5428; p < 0.0001) than restlessness/irritability alone (χ(2) = 151.278; df = 2, p < 0.0001; R (2) = 0.4133). The overlap of gambling withdrawal‐like symptoms with substance use withdrawal (11%) and depressive symptoms (34%) failed to fully account for these associations with gambling disorder status. Future PGD conceptualization and potential criteria revisions for DSM‐V may warrant a broader inclusion of gambling withdrawal‐like symptoms. Copyright © 2009 John Wiley & Sons, Ltd.